A COSMOPOLITAN CRITIQUE ON STATE REFUSAL TO EXERCISE UNIVERSAL JURISDICTION - Albar, Rafsi Azzam Hibatullah; Poerawinata, Nyi Raden Calvinca Naomi (Mimbar Hukum, 2024)
Abstract Despite some controversy surrounding its enforcement, universal jurisdiction is a well-known doctrine within the realm of international criminal law. While only a small number of countries have actively prosecuted grave human rights violations happening elsewhere within their domestic courts, there is still the overlooked question of whether a state could refuse the right to exercise this doctrine. In response to a recent decision by the Indonesian Constitutional Court which makes this an urgent inquiry yet addressed by existing prescriptive scholarship, we borrow the propositions of scholars of the cosmopolitan movement to argue that the answer is an unequivocal ‘no’. We invoke philosophies that shape cosmopolitanism in this regard—natural law, social contract, and global justice—to not only offer a response for the inquiry but also stress its exigency. Using the same core premises, we further disprove common counter-narratives that, if entertained, would have detrimental effects on accountability and the spirit of international law at large. Abstrak Terlepas dari beberapa kontroversi seputar penegakannya, yurisdiksi universal merupakan doktrin yang terkenal dalam ranah hukum pidana internasional. Meskipun hanya sedikit negara yang secara aktif menuntut pelanggaran HAM berat yang terjadi di negara-negara lain melalui pengadilan domestik mereka, masih ada pertanyaan yang terabaikan, yaitu apakah suatu negara dapat menolak untuk menggunakan doktrin ini. Menanggapi keputusan Mahkamah Konstitusi Indonesia yang baru-baru ini yang membuat pertanyaan ini menjadi pertanyaan yang mendesak dan belum dijawab oleh kesarjanaan preskriptif yang ada, kami meminjam ide-ide dari para cendekiawan dari gerakan kosmopolitan untuk berargumen bahwa jawabannya adalah “tidak”. Kami menggunakan filosofi yang membentuk kosmopolitanisme dalam hal ini-hukum alam, kontrak sosial, dan keadilan global-untuk tidak hanya menawarkan jawaban atas pertanyaan tersebut-tetapi juga menekankan urgensinya. Dengan menggunakan premis-premis inti yang sama, kami lebih lanjut membantah kontra-narasi umum yang, jika dituruti, akan berdampak buruk pada akuntabilitas dan semangat hukum internasional pada umumnya.